Altered intraperitoneal immune microenvironment in patients with peritoneal metastases from gastric cancer - Takahashi, Kazuya; Kurashina, Kentaro; Yamaguchi, Hironori; Kanamaru, Rihito; Ohzawa, Hideyuki; Miyato, Hideyo; Saito, Shin; Hosoya, Yoshinori; Lefor, Alan Kawarai; Sata, Naohiro; Kitayama, Joji (Frontiers in Immunology, 2022)
Background: The peritoneal cavity contains many site-specific immune cells which constitute a unique immune microenvironment. However, it is unclear how the local immune signature is altered in patients with peritoneal metastases (PM). Methods: Peritoneal lavage fluid or ascites were obtained from 122 patients with various stages of gastric cancer (GC). Cells recovered from peritoneal fluids were immunostained with mAbs for lymphocyte-, macrophage- and tumor cell-specific antigens and the frequencies of leukocyte subsets and antigen expression levels were evaluated with multi-color flowcytometry. Results: The proportions of CD8(+) T cells, CD3(+)CD56(+) NKT-like cells, and CD3(-)CD56(+) NK to CD45(+) leukocytes were significantly reduced in patients with PM compared to those without PM. In patients with PM, the rates of CD8 (+) T cells and NKT-like cells correlated inversely with the tumor leukocyte ratio (TLR), the relative frequency of CD326(+) tumor cells to CD45(+) leukocytes. In contrast, the proportion of CD19(+) B cells was significantly increased in patients with PM, and their proportion correlated positively with the TLR and peritoneal carcinomatosis index (PCI) score. In patients with PM, CD14(+) macrophages tended to be increased with enhanced expression of CD14, CD16 and a M2-macrophage marker, CD163. In particular, macrophages in patients with high TLR contained many granules with high side scatter and CD14 expression in their flow profile compared to those without PM. Conclusion: PM are accompanied by a drastic change in phenotypes of lymphocyte and macrophage in the peritoneal cavity, which might be involved in the development and progression of intraperitoneal tumor growth.